The performance of microenterprises in Palu City: financial literacy moderates the influence of access to capital and digital payment - Prasetia, Tadir Eko; Nurdin, Djayani; Kadang, Juliana (Manajemen dan Bisnis, 2025)
This research is aimed at identifying and analyzing the key factors of economic access, digital payments, and financial literacy as mediation variables towards the performance of microenterprises in Palu City. The type of research used is quantitative research. The population in this study is the entire microenterprise in Palu City. The analysis tool used in this study is Partial Least Squares (PLS) 3.0 with a sample of 278 respondents. Data collection using a questionnaire through Google Forms. The results of the research show that (1) access to financial assets has a positive and significant influence on the performance of micro enterprises, (2) digital payments have a positive influence and a significant effect on micro enterprise performance, (3) financial literacy has a negative influence (enhancing) as moderation of the relationship between access to finance and performance of micropartnerships, and (4) financial literature has a positive impact (enforcing) in terms of moderating the relation between digital payments and the performance of microenterprises in the city of Palu.